Susan B. Anthony Foundation (Washington, D.C.) records - Susan B. Anthony Foundation (Washington, D.C.); Anthony League of the District of Columbia; District of Columbia Woman Suffrage Association
Correspondence, bylaws and constitution, minutes, reports, financial records, membership lists, a scrapbook, clippings, printed matter, and other records. Includes biographical material concerning Susan B. Anthony, records of the District of Columbia Woman Suffrage Association, and material relating to Anna E. Hendley, founder and president of the foundation. Correspondence relates to the District of Columbia Federation of Women's Clubs, the General Federation of Women's Clubs, the Juvenile Protective Association of the District of Columbia, and the National League of Women Voters.
Organization founded to promote women's issues; from its establishment in 1912 until 1924 was known as the Anthony League of the District of Columbia.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Anthony, Susan B. -- 1820-1906.; Hendley, Anna E; District of Columbia Federation of Women's Clubs; General Federation of Women's Clubs; Juvenile Protective Association of the District of Columbia; National League of Women Voters (U.S.); Women; Women -- Suffrage